Determination of 5-caffeoylquinic acid (5-CQA) as one of the major classes of chlorogenic acid in commercial tea and coffee samples - Grujić-Letić Nevena; Rakić Branislava; Šefer Emilia; Rakić Dušica; Nedeljković Ivan; Kladar Nebojša; Božin Biljana (Vojnosanitetski Pregled)
Background/Aim. Tea and coffee are one of the most widely consumed beverages in the world due to their beneficial health effects which are largely associated with their phenolic compounds composition, including chlorogenic acid. The main aim of this study was to determine 5-caffeoylquinic acid (5-CQA), as one of the major classes of chlorogenic acid, in various commercial tea and coffee samples present at the Serbian market. Methods. A high-performance liquid chromatography (HPLC) method for determination of 5-CQA in plant extracts was applied to determine the content of this active compound in commercial tea and coffee samples. Mobile phase was aqueous 1.5% acetic acid - methanol (80:20, v/v) with the flow rate of 0.8 mL/min. Run time was 15 min and column temperature 25°C. The detection was performed at 240 nm. Results. The HPLC method was modified and revalidated. The 5-CQA content varied depending on the type of tea (white, green, black tea and mate) and the processing technology. Green tea had the highest 5-CQA content (16 mg/100 mL) among the analyzed tea samples. The content of 5-CQA in coffee samples ranged 0-36.20 mg/g of coffee and 0-46.98 mg/100 mL of beverage, showing that the content varied depending on the type of coffee, coffee processing technology and the formulation. Conclusion. The modified and revalidated HPLC method showed a good accuracy, repeatability, selectivity and robustness. The highest amount of 5-CQA was determined in green tea in comparison to white, black and mate tea because the increased oxidation level decreases the amount of 5-CQA. The obtained results for commercial coffee samples indicated that the formulation was the most important factor determining the amount of 5-CQA. It can be concluded that plant material selection, processing conditions and formulation have great influence on the amount of chlorogenic acid (5-CQA) in the final tea and coffee products. [Projekat Ministarstva nauke Republike Srbije, br. OI 172058]